Can dye-sensitized solar cells generate electricity in the dark?. (March 2017) - Tang, Qunwei; Wang, Jing; He, Benlin; Yang, Peizhi
Abstract: Energy harvest requirements for future photovoltaic devices include high efficiency, cost-effectiveness, and persistent power-generation in all weathers. To address this issue, we present here all-weather dye-sensitized solar cells that can generate electricity in the daytime and in the dark by incorporating long persistence phosphors (LPPs) into mesoscopic TiO2 ( m -TiO2 ) photoanodes. When suffered simulated sunlight (air mass 1.5, 100 mW cm −2 ) illumination, the all-weather solar cell having fluorescent-emitting m -TiO2 /LPP photoanode yields a maximal photoelectric conversion efficiency of 10.08%. The unabsorbed red and infrared light across dye-sensitized m -TiO2 layer is stored in LPP phosphors, and is subsequently converted into monochromatic fluorescence for persistent dye illumination at dark conditions, yielding a maximized photoelectric conversion efficiency up to 26.69% as well as duration lasting for several hours. Graphical abstract: Dye-sensitized solar cells that can generate electricity in the daytime and dark are fabricated by combining long persistence phosphors with mesoscopic TiO2 photoanodes. Highlights: All-weather dye-sensitized solar cells are realized. Long persistence phosphors are used to store solar energy and release at dark. A photoelectric conversion efficiency at dark is as high as 26.69%. The all-weather solar cells are promising for future power generation devices.